Ileal free flap for hypopharynx reconstruction – case series - Tintinago-Londoño Luis Fernando; Candelo Estephania; Guzmán Tania; Victoria-Morales William (Innovative Surgical Sciences)
Reconstructing the hypopharynx while preserving the larynx poses a complex surgical challenge due to the limited space and the high position of the hypopharynx in the neck. We present our experience with hypopharyngeal reconstruction and larynx preservation using an ileal free flap.